Synthesis of polypyrrole/Ni-doped TiO 2 Nanocomposites (NCs) as a protective pigment in organic coating - Mahmoudian, M.R.; Alias, Y.; Basirun, Wan Jefrey (2011)
This study reports the synthesis of polypyrrole/Ni-doped TiO 2 nanocomposites (NCs) as a protective pigment in organic coatings. Polypyrrole/Ni-doped TiO 2 NCs were prepared by in situ chemical oxidative polymerization of pyrrole monomer in the presence of Ni-doped TiO 2 nanoparticles (NPs) with ammonium persulfate (APS) as oxidant. Field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM) result show a core-shell structure of the pigments. The XRD results indicate that the average crystalline size of Ni-doped TiO 2 NPs is larger than TiO 2 NPs while the sizes of polypyrrole/TiO 2 NCs and polypyrrole/Ni-doped TiO 2 NCs were 93.46 ± 0.06 and 26.16 ± 0.06 nm respectively. Hence the thickness of the shell in the core-shell incorporating the Ni-doped/TiO 2 NPs was very thin and the area of synthesized PPy is increased. The electrochemical impedance spectroscopy (EIS) results show that increasing the area of synthesized polypyrrole in the presence of Ni-doped-TiO 2 NPs can increase its ability to interact with the ions liberated during the corrosion reaction of steel in the presence of NaCl. © 2010 Elsevier B.V. All rights reserved.